Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

"To every Q-matrix $q$ corresponds a unique Markov process." I'm trying to understand Klenke's proof of the "existence" part of this proposition, namely that given a Q-Matrix $q$, there exists a Markov process $\mathfrak{X}$, whose Q-Matrix is $q$. (Theorem 17.25, see below)

Listed below is the beginning of his proof (the rest, which is irrelevant to my current question, can be found here). What i fail to figure out is how to show that $\mathfrak{X}$ (defined in the proof below) is a Markov process. I recalled Klenke's definition of a Markov process in a previous post.


Relevant definitions

  1. Let $E$ be a non-empty, countable set.

  2. A Q-Matrix in $E$ is a function $q:E\times E\rightarrow\mathbb{R}$ such that

    i) $q(e,d)\geq0$ for all $e,d\in E$,

    ii) $q(e,e)=-\sum_{e\neq d}q(e,d)$,

    iii) $0<\lambda:=\sup_{e\in E}|q(e,e)|<\infty$

  3. Given an $E$-valued stochastic process $X=(X_t)_{t\in[0,\infty)}$ and a function $q:E\times E\rightarrow\mathbb{R}$, $q$ is the Q-matrix of $X$ iff for all $e,d\in E$ $$\lim_{t\downarrow0}\frac{1}{t}\left(\mathrm{P}_e[X_t=d]-\delta_{e,d}\right)=q(e,d)$$ ($\delta$ is Kronecker's delta)

Theorem 17.25 $q$ is a Q-matrix $\implies$ $q$ is the Q-matrix of a unique Markov process.

Proof (This is only the beginning of Klenke's proof; the rest can be found here.)

Let $I$ be the unit matrix on $E$. Define $$p(e,d):=\frac{1}{\lambda}q(e,d)+I(e,d)\space\space\mathrm{for\, }e,d\in E.$$

Then $p$ is a stochastic matrix and $q=\lambda(p-I)$.

Let $\left(Y=(Y_n)_{n\in\mathbb{N}_0},(\mathrm{P}_e^Y)_{e\in E}\right)$ be a discrete Markov chain over the measurable space $S_Y=(\Omega_Y,\mathcal{A}_Y)$ with transition matrix $p$ and let $\left(T=(T_t)_{t\geq0},(\mathrm{P}_n^T)_{n\in\mathbb{N}_0}\right)$ be a Poisson process over the measurable space $S_T=(\Omega_T,\mathcal{A}_T)$ with rate $\lambda$. We may assume w.l.g. that $Y$ and $T$ are defined over the product space $S_Y\otimes S_T$.

Set $X_t:=Y_{T_t}$ and $\mathrm{P}_e:=\mathrm{P}_e^Y\otimes\mathrm{P}_0^T$. Then $\mathfrak{X}:=\left(X=(X_t)_{t\geq0},(\mathrm{P}_e)_{e\in E}\right)$ is a Markov process and $$p_t(e,d):=\mathrm{P}_e[X_t=d]=\sum_{n=0}^\infty\mathrm{P}_0^T[T_t=n]\mathrm{P}_e^Y[Y_n=d]=e^{-\lambda t}\sum_{n=0}^\infty \frac{\lambda^nt^n}{n!}p^n(e,d)$$

share|improve this question
add comment

1 Answer

up vote 0 down vote accepted

We wish to show that $\mathfrak{X}$ is a Markov process. According to the definition of a Markov process we need to show that the Markov property holds, namely $$\forall e\in\mathbb{N}_0\forall s,t\in [0,\infty)\forall B\subseteq\mathbb{N}_0,\space \mathrm{P}_e[X_{s+t}\in B|\mathcal{F}_s]=\mathrm{P}_{X_s}[X_t\in B]\space\space\mathrm{P}_e\mathrm{-a.s.}$$ (To qualify as a Markov process, $\mathfrak{X}$ must additionally be shown to satisfy that $$\kappa:\mathbb{N}_0\times\mathcal{B}(\mathbb{N}_0)\rightarrow[0,1],\space\space(e,B)\mapsto\mathrm{P}_e[X\in B]$$ be a stochastic kernel, but this is obvious if we recall that the implicit topology on $\mathbb{N}_0$ is taken to be the discrete one, hence $\mathcal{B}(\mathbb{N}_0)=\mathbb{P}(\mathbb{N}_0)$.)

Let $e\in\mathbb{N}_0$, $s,t\in[0,\infty)$ and $B\subseteq\mathbb{N}_0$. Since probabilities as well as conditional probabilities are $\sigma$-additive and since $\mathbb{N}_0$ is countable, we may assume w.l.g. that $B$ is a singleton: $B=\{j\}$. So we need to show: $$\mathrm{P}_e[X_{s+t}=j|\mathcal{F}_s]=\mathrm{P}_{X_s}[X_t=j]\space\space\mathrm{P}_e\mathrm{-a.s.}$$

By definition of "conditional probability", this amounts to showing that for every $G\in\mathcal{F}_s$, $$\mathrm{P}_e[\{X_{s+t}=j\}\cap G]=\intop_G \mathrm{P}_{X_s}[X_t=j]\space\mathrm{dP}_e\space\space(*)$$

By Dynkin's $\pi$-$\lambda$ theorem it suffices to consider a $G$ of the form $$G=\bigcap_{i=0}^n \{X_{u_i}=k_i\}\space\space(**)$$ for some $n\in\mathbb{N}_0$, $0 \leq u_0 < u_1 < \cdots < u_n \leq s$ and $k_0, k_1, \dots, k_n\in\mathbb{N}_0$.

Suppose $G$ takes this form. We are content with restricting our attention to the case $n=0$, as the general case is proved quite analogously. Assume therefore $n=0$ and let $u\in[0,s]$ and $k\in\mathbb{N}_0$. We have $$\begin{align}\intop_{X_u=k}\mathrm{P}_{X_s}[X_t=j]\space\mathrm{dP}_e &=\sum_{m=0}^\infty\space\intop_{X_u=k\atop X_s=m} \mathrm{P}_{X_s}[X_t=j]\space\mathrm{dP}_e\\ &=\sum_{m=0}^\infty\space\intop_{X_u=k\atop X_s=m} \mathrm{P}_m[X_t=j]\space\mathrm{dP}_e\\ &=\sum_{m=0}^\infty\space\mathrm{P}_e[X_u=k, X_s=m]\mathrm{P}_m[X_t=j]\end{align}$$

If we can show that for all $m\in\mathbb{N}_0$, $$\space\mathrm{P}_e[X_u=k, X_s=m]\mathrm{P}_m[X_t=j]=\mathrm{P}_e[X_u=k, X_s=m, X_{s+t}=j]$$ we're done. Therefore, let $m\in\mathbb{N}_0$.

Now, using the facts that under $\mathrm{P}_e=\mathrm{P}_e^Y\otimes\mathrm{P}_0^T$, $Y$ and $T$ are independent and that $T$, being a Poisson process, has additive, independent increments, we get

$$\begin{align}&\mathrm{P}_e(Y_{T_u}=k, Y_{T_s}=m)\mathrm{P}_m(Y_{T_t}=j)\\ &=\sum_{a,b,c=0}^\infty \mathrm{P}_e(Y_a=k, Y_b=m, T_u=a, T_s=b)\mathrm{P}_m(Y_c=j, T_t=c)\\ &=\sum_{a,b,c=0}^\infty \mathrm{P}^Y_e(Y_a=k, Y_b=m)\mathrm{P}_m^Y(Y_c=j)\mathrm{P}_0^T(T_u=a)\mathrm{P}_0^T(T_{s-u}=b-a)\mathrm{P}_0^T(T_t=c) \end{align}$$

and

$$\begin{align}&\mathrm{P}_e(Y_{T_u}=k, Y_{T_s}=m, Y_{T_{s+t}}=j)\\ &=\sum_{a,b,c=0}^\infty\mathrm{P}_e(Y_a=k, Y_b=m, Y_{b+c}=j, T_u=a, T_s=b, T_{s+t}=b+c)\\ &=\sum_{a,b,c=0}^\infty\mathrm{P}_e^Y(Y_a=k, Y_b=m, Y_{b+c}=j)\mathrm{P}_0^T(T_u=a)\mathrm{P}_0^T(T_{s-u}=b-a)\mathrm{P}_0^T(T_t=c) \end{align}$$

Therefore, it suffices to show that for all $a,b,c\in\mathbb{N}_0$, $$\mathrm{P}_e^Y(Y_a=k, Y_b=m, Y_{b+c}=j)=\mathrm{P}^Y_e(Y_a=k, Y_b=m)\mathrm{P}_m^Y(Y_c=j)$$ Note that since $u\leq s$, $T_u\leq T_s$, so we can safely assume that $a\leq b$.

But since $\left(Y, (\mathrm{P}_e^Y)_{e\in\mathbb{N}_0}\right)$ is a Markov chain, we get from the Markov property (2nd equation below) $$\begin{align}\mathrm{P}_e^Y(Y_a=k, Y_b=m, Y_{b+c}=j)&=\mathrm{E}_e^Y\left(\mathrm{P}_e^Y(Y_{b+c}=j|\mathcal{F}_b)\space; Y_a=k, Y_b=m\right)\\ &=\mathrm{E}_e^Y\left(\mathrm{P}_{Y_b}^Y(Y_c=j)\space; Y_a=k, Y_b=m\right)\\ &=\mathrm{E}_e^Y\left(\mathrm{P}_m^Y(Y_c=j)\space; Y_a=k, Y_b=m\right)\\ &=\mathrm{P}_m^Y(Y_c=j)\mathrm{P}_e^Y\left(Y_a=k, Y_b=m\right)\end{align}$$

which concludes the proof. $\square$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.